Informação, conhecimento e comunicação nas organizações do conhecimento - Porém, Maria Eugênia [UNESP]; Guaraldo, Tamara de Souza Brandão (My University, 2012)
Reflection on the role of information, knowledge and communication on "knowledge organizations". The organizations called "knowledge organizations" need to be incurred in implementing significant changes in its organizational culture to meet the requirements of innovation - intrinsic to knowledge management. For this, we consider that these changes are possible to occur to the extent that organizations understand that despite the particularities of information, knowledge, and they represent a triad whose elements are inseparable in the construction of knowledge organizations.

Reflexão sobre o papel da informação, do conhecimento e da comunicação em “organizações do conhecimento”. As organizações denominadas “organizações do conhecimento” para se constituírem necessitam implantar mudanças significativas em sua cultura organizacional para responderem às exigências de inovação – característica intrínseca à gestão do conhecimento. Para tanto, consideramos que essas mudanças são possíveis de acontecer na medida em que as organizações compreenderem que, apesar das particularidades existentes entre informação, conhecimento e comunicação eles representam uma tríade cujos elementos são inseparáveis na construção de organizações do conhecimento.
Information, knowledge and communication in knowledge organizations
Keywords: Information; Knowledge; Communication; Knowledge Management; Organization communication; Knowledge Organizations; Informação; Conhecimento; Comunicação; Gestão do conhecimento; Comunicação organizacional; Organizações do conhecimento